Pengaruh Pemberian Konsentrasi Cuka Kayu dan Pupuk Hayati Mikoriza Arbuskula terhadap Pertumbuhan dan Hasil Tanaman Kedelai Edamame (Glycine max L.Merrill). - Rohanis Yuliyati; Ida Bagus Komang Mahardika; Anak Agung Sagung Putri Risa Andriani (GEMA AGRO, 2023)
This study aims to analyze the effect of giving concentrations of wood vinegar and arbuscular mycorrhizal biofertilizers on the growth and yield of soybean Edamame (Glycine max L. Merrill.). As well as to determine the interaction of giving a combination of wood vinegar and mycorrhizal biofertilizers on the growth and yield of Edamame soybean plants (Glycine max L. Merrill.). This research was conducted in the experimental garden of the Faculty of Agriculture, Warmadewa University, Jalan Terompong No.24, Sumerta Kelod, East Denpasar District, Denpasar City from May to August 2022. The research method used was a Randomized Block Design (RAK) with 2 factors arranged factorial . The first factor was the administration of wood vinegar (C), which consisted of 4 levels, namely C0 = Control (0% wood vinegar concentration), C1 = 2% wood vinegar concentration, C2 = 4% wood vinegar concentration, C3 = 6% wood vinegar concentration. the second factor used biological mycorrhiza (M) fertilizer which consisted of 5 treatment levels, namely M0 = Control (0 g.polybag-1), M1 = 5 g.plant-1, M2 = 10 g.plant-1, M3 = 15 g .plant-1, M4 = 20 g.plant-1 was repeated 3 times so that 60 polybags were needed. The results of statistical analysis showed that the dose of mycorrhizal biofertilizer had a significant effect (P <0.05) on the highest number of flowers per plant obtained in the M3 treatment (15 g.plant-1), namely 46.25 buds, an increase of 21.08% compared to mycorrhizal fertilizer treatment M0 (0 g.plant-1) namely 36.50 buds. The highest number of pods per plant was obtained in the M3 treatment (15 g.plant-1), namely 43.25 pods, an increase of 21.39% compared to the M0 mycorrhizal fertilizer treatment (0 g.plant-1), ie 34.00 pods. Keywords: edamame soybean, arbuscular mycorrhizal fertilizer, wood vinegar